Pengaruh Jenis Media Tanam Dan Lama Perendaman Benih Dalam Air Hangat Terhadap Bibit Pepaya (Carica papaya L.) - Maxsimus Ulu; Roberto I.C.O. Taolin; Regina Seran (Fakultas Pertanian, Universitas Timor, 2019)
It has been done to determine the effect of soaking time on papaya seeds and to test the type of manure and husk charcoal on the growth of papaya seeds. The research implemented in July-September 2018 in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kefamenanu City District, TTU Regency, using a Randomized Block Design (RAK) with two faktors, namely the first faktor is the length of soaking the seeds in warm water which consists of of 3 (three) levels, 30 minutes, 60 minutes, 120 minutes. The second faktor consists of 4 (four) levels, namely control of empty land, soil + husk charcoal, soil + manure, soil + husk charcoal + cow manure. All treatment combinations were repeated 3 times so that there were 36 experimental plots. The results showed that papaya plants immersed in warm water for 120 minutes and treated with soil planting media + husk charcoal + cow manure could increase the growth of papaya plants which could be expressed in the form of the highest plant height, the highest number of leaves and the largest diameter.